Numerical simulation of the motions and forces of a moored ship in Leixões harbour - L. Pinheiro (2015)
Ships berthed inside sheltered basins can experience excessive movements due to waves. The paper presents an integrated numerical tool that interconnects several numerical models to reproduce the most relevant physical phenomena associated to wave action on a moored ship, the resulting ship movements and the forces on mooring lines and fenders. A new methodology was developed to determine the hydrodynamic forces on the ship.A non-linear phase resolving Boussinesq model is used to propagate waves from outside the harbour to wherever desired location inside the harbour. A modified version of a 3D panel method model computes the hydrodynamic coefficients of the ship, whereas the Haskind relations determine the wave forces on the ship. The time series of the moored ship motions and forces on moorings are obtained with another numerical model. This new methodology is used to replicate the scale model tests of a moored tanker inside Leixões Harbour. (c) 2016 Taylor & Francis Group, London.